Data resources for thermophysical properties of metals and alloys, Part 1: Structured data capture from the archival literature. (March 2017) - Wilthan, Boris; Pfeif, Erik A.; Diky, Vladimir V.; Chirico, Robert D.; Kattner, Ursula R.; Kroenlein, Kenneth
Abstract: In support of the continuous scientific and industrial need for accessible and high-quality thermophysical property data for metals and alloy systems, NIST/TRC is expanding its data archiving and critical evaluation activities to include this area. As part of this effort, a new data-capture software tool was developed. The new tool is described here in detail, including a list of supported properties, descriptions, and justification for capture of specific metadata. The key design features are: the separation of experimental results from author interpretations, a data-capture structure that mimics that of typical published experimental data, extensive and flexible capabilities for phase identification, well-structured capture of metadata related to sample characterization, and quantitatively defined uncertainties. This work (Part 1) marks the completion of an essential first step in the development of a freely available data resource of experimental and critically evaluated thermophysical properties for metallic systems. The next article in this series (Part 2) will describe the first implementation of data analysis tools, as well as channels for dissemination of results to users through online web services and offline software.